2020
DOI: 10.9734/irjpac/2020/v21i1530249
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Nutrient Management for Enhancing Crop Productivity

Abstract: Nutrient management plays a crucial role in achieving self-sufficiency in food grain production. High price index of chemical fertilizers coupled with mount pollution problem gave rise to interest in precision nutrient management tools. Site specific nutrient management (SSNM) increases and maintains the yield by optimizing the balance between supply and demand of nutrients. Nutrient application as per SSNM concept resulted in significantly higher grain yields of maize, rice, wheat and other important crop ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…Earlier, several findings confirmed that rice grain and straw yield were influenced by the crop establishment method [67] and nitrogen management [68]. In our present study, the difference in grain yield of rice with DSR method between two years was probably due to climatic variation, i.e., higher rainfall in 2017 immediately after seeding and during the crop establishment period.…”
Section: Yield and Yield Parametersupporting
confidence: 81%
“…Earlier, several findings confirmed that rice grain and straw yield were influenced by the crop establishment method [67] and nitrogen management [68]. In our present study, the difference in grain yield of rice with DSR method between two years was probably due to climatic variation, i.e., higher rainfall in 2017 immediately after seeding and during the crop establishment period.…”
Section: Yield and Yield Parametersupporting
confidence: 81%
“…The treatments involved in enhanced nitrogen produced more grain in a single row may be due to the application of fertilizer fulfills the nutrient demand at critical growth stage attributed to better growth and partitioning of photosynthates. This line was earlier confirmed by Biradar et al [11] and Bana et al [12]. The interaction effect due to tillage practices and nitrogen levels on number of kernels row -1 was found to be nonsignificant (Table 3).…”
Section: Kernel Number Row -1supporting
confidence: 82%
“…Improvement in leaf chlorophyll content due to application of 122 kg N ha -1 at LCC threshold 5 and SPAD 50 over fixed time application of 125 kg N ha -1 supports improved photosynthetic rate leading to higher growth and biomass production. The enhanced growth with LCC based nitrogen application was also reported by Bana et al, (2020). The LCC threshold 5 and SPAD 50 need-based application of 122 kg N ha -1 significantly increased yield attributes viz., number of grains cob -1 , grain weight plant -1 and 1000-grain weight and ultimately grain (3069 kg ha -1 ) and stover yield (4045 kg ha -1 ) of maize as compared to fixed time application of 125kg N ha -1 (Table 4).…”
Section: Effect On Growth and Yieldsupporting
confidence: 58%